Evaluation Of Time To Achieve Dry Weight Using Body Composition Monitor, Hypertension Management And Prevalence Of Depression Among Hemodialysis Patients In Kelantan Malaysia - Khan, Amjad (2018)
Almost 60-90 % hemodialysis (HD) patients are hypertensive. Achieving and maintaining dry weight appears to be an effective strategy for controlling and maintaining normotension among hypertensive patients on HD therapy. Body composition monitor (BCM) helps estimate patient hydration status and dry weight accurately. For this purpose, the present study aimed to determine the time at which the majority of patients achieve postdialysis dry weight using bioimpedance spectroscopy (BIS) at Hospital Universiti Sains Malaysia (HUSM), a tertiary care hospital and a group of private centers outside the hospital in Kelantan, Malaysia. A total of 220 HD patients were prospectively assessed for fluid overload using the Fresenius body composition monitor (BCM). BCM readings were taken at 30 and 45 minutes postdialysis. Among the 220 patients included in this study, 120 (54.5%) achieved a euvolemic state at 30 minutes, and 25 (11.4%) achieved it at 45 minutes according to the BCM. In the multivariate analysis, vascular access other than arteriovenous fistula (AVF) (OR=0.286, p value=0.049) and cardiovascular disease (OR=0.384, p value=0.026) had a statistically significant negative association and receiving hemodialysis therapy at HUSM (OR=2.705, p value=0.008) had a statistically significant positive association with achieving a euvolemic state at 30 minutes. Moreover, we evaluated hypertension control and factors influencing hypertension control among euvolemic hypertensive hemodialysis patients.